Effect of Transformational Leadership Style on Innovative Work Behavior at Higher Education Level - Mamona Tanveer; Dr. Amna Saleem (Indus Journal of Social Sciences, 2025)
Transformational leadership is widely recognized as a key driver in educational settings. The purpose of this study is to examine the ways in which transformational leadership styles promote motivation, creativity, and institutional growth among college teachers. Transformative leaders provide vision, intellectual stimulation, individualized attention, and idealized influence in order to innovate teaching practices. In this study, we investigate how transformational leadership influences teachers’ willingness to adopt innovative approaches in their daily work. A quantitative research design was used to survey 252 college teachers at the Institute of Southern Punjab. Inferential statistics (regression) were used with a randomly selected sample to analyze the data via SPSS. It has been found that transformational leadership is positively correlated with innovative work behaviors, which supports the idea that principals who foster trust, encourage creativity, and provide mentorship enhance teachers’ innovative capabilities. The research also indicates that there is a lack of institutional support, rigid administrative structures, and resistance to change. According to the results of the study, educational administrators should cultivate transformational leadership to create a culture of innovation. It is recommended that leadership training programs be established, policy reforms be implemented in order to encourage autonomy, and institutional mechanisms to promote creativity be implemented.